Observers’ Reflection Level and Categories on Lesson Study Activities in English Classroom at SMP Negeri 2 Bua - Rahmawati Upa; Sri Rahayu; Nuur Insan Tangkelangi (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2023)
Reflection is one stage in Lesson Study activities. It is a very important stage since further effort to improve the learning process depends on the sharpness of the analysis given by the observers in reflection. This research aims at describing the category and the level of observers’ reflection on lesson study activities. This research was conducted in SMP Negeri 2 Bua by using qualitative method. In order to categorize the categories and the level of teacher’s reflection, the researchers used the instrument developed by (Ono et al., 2013) which are divided into 5 reflection categories, those are; 1) teaching and learning strategies, 2) teacher’s behavior, 3) Lesson experienced by students (students’ learning, students’ behavior, and interaction between students), 4) achievement of lesson and curriculum objectives, 5) logistic; management planning, and 4 reflection levels (1, 2, 3, 4). The finding of the research shows that from three times reflection, most of the observers’ comment on reflection was categorized into the third category; that is lessons as experienced by students and this category is in level 1. It means that most of the observers’ comment was focused on describing the students’ experiences/behavior but not including their explanation about the reason of the possible cause for the observation. In the end of this research, some recommendations are drawn for the future reflection.